2018
DOI: 10.18494/sam.2018.1795
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Responsivity and Quantum Efficiency of p-Si/i-β-FeSi2/n-Si Photodiodes

Abstract: Keywords: p-Si/i-β-FeSi 2 /n-Si photodiode, responsivity, quantum efficiencyIn this study the responsivity and quantum efficiency of p-Si/i-β-FeSi 2 /n-Si doubleheterostructure photodiodes and p-Si/i-Si/n-Si photodiodes are investigated by self-developed analytical methods. The dark current densities of both β-FeSi 2 and Si p-i-n photodiodes under the reverse bias condition are calculated by solving the diffusion current densities of minority carriers. The photocurrent densities of both p-i-n photodiodes under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The U-grooved structure photodetector exhibits a much higher performance because the large light-detecting surface area increases the number of photogenerated carriers at the surface of the U-grooved structure, preventing charge-carrier recombination. (30,35,36) Table 2 shows a comparison of the important parameters of the MSM and UMSM photodetectors. It was found that the electrical and optical properties of the UMSM photodetector were superior to those of the MSM photodetector of the same size: at an incident optical power of 6 mW, the UMSM photodetector had a photocurrent of 71.05 µA, approximately 2.5 times more than that of the MSM photodetector (28.92 µA).…”
Section: Personal Computermentioning
confidence: 99%
“…The U-grooved structure photodetector exhibits a much higher performance because the large light-detecting surface area increases the number of photogenerated carriers at the surface of the U-grooved structure, preventing charge-carrier recombination. (30,35,36) Table 2 shows a comparison of the important parameters of the MSM and UMSM photodetectors. It was found that the electrical and optical properties of the UMSM photodetector were superior to those of the MSM photodetector of the same size: at an incident optical power of 6 mW, the UMSM photodetector had a photocurrent of 71.05 µA, approximately 2.5 times more than that of the MSM photodetector (28.92 µA).…”
Section: Personal Computermentioning
confidence: 99%